Regime transformations and global realignments : Indo-European dialogues on the post-cold war world - Ahuja, Kanta; Coppens, Huub; Wusten, Herman van der (Indo-Dutch studies on development alternatives, 1993)
Papers presented at a seminar organized by Indo-Dutch Programme on Alternatives in Development in Netherlands, December 7-10, 1992.